Al Maqasid Al Shariah - Bakri, Husna Najihah; Mohd Salehudin, Mardiyyah Mutmainnah; Mohd Aznan, Anees Mysarah; Abdul Hamid @ Sulaiman, Nur Aina Adlina; Hanapi, Nureen Hafiza; Amram, Adriana Izzah (2025)
The science of objectives (maqasid) is a science that studies evidence in general and specific legal rulings. It focuses on studying the meanings and wisdom for which legal rulings were legislated. These may be general or specific. The science of objectives is, in fact, a science linked to both the principles of jurisprudence and Islamic jurisprudence. The objectives of Islamic law can be defined as: "The meanings and rulings established by the Wise Lawgiver to achieve the interests of mankind and ward off harm from them." They encompass the Kalabrian principles related to the preservation of humanity and society in various aspects, whether religious, worldly, or otherworldly. Accordingly, there are two types of legal objectives: literal meanings and general customary meanings. Both must be fixed, apparent, precise, and consistent. We then examined Sharia and found that it does not take into account illusions and fantasies, and ordered their rejection. We therefore ruled that illusions are unsuitable for legitimate purposes.